A Novel Pretreatment Regimen for Breakthrough Radiocontrast Media Anaphylaxis in Cardiac Patients. Issue 4 (December 2016) - Montandon, Shari V.; Petrov, Andrej A.; Fajt, Merritt L.
Abstract : Background: Radiocontrast media allergy is a severe and potentially life-threatening condition. This creates a clinical dilemma for cardiac patients who require urgent interventions with radiocontrast media. Several pretreatment regimens have been suggested for patients with prior immediate hypersensitivity reactions to radiocontrast media. Despite using pretreatment regimens, breakthrough reactions have been reported in 2.1%–18% of patients with radiocontrast media allergy. Little is known about management of patients with a history of breakthrough radiocontrast media anaphylaxis who require urgent lifesaving procedures. Methods: We report a retrospective analysis of 2 cardiac cases with a history of breakthrough radiocontrast media anaphylaxis despite standard pretreatment. These patients required urgent cardiac intervention with the use of radiocontrast media. Results: We present a novel pretreatment regimen for high-risk cardiac patients with breakthrough radiocontrast media anaphylaxis despite prior pretreatment who need urgent coronary interventions. Conclusion: This protocol is both safe and effective in mitigating anaphylaxis in cardiac patients.